Brief Report: Heterogeneous Preferences for Care Engagement Among People With HIV Experiencing Homelessness or Unstable Housing During the COVID-19 Pandemic. (1st June 2022) - Imbert, Elizabeth; Hickey, Matthew D.; Del Rosario, Jan Bing; Conte, Madellena; Kerkhoff, Andrew D.; Clemenzi-Allen, Angelo; Riley, Elise D.; Havlir, Diane V.; Gandhi, Monica
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background/Setting: In San Francisco, HIV viral suppression is 71% among housed individuals but only 20% among unhoused individuals. We conducted a discrete choice experiment at a San Francisco public HIV clinic to evaluate care preferences among people living with HIV (PLH) experiencing homelessness/unstable housing during the COVID-19 pandemic. Methods: From July to November 2020, we conducted a discrete choice experiment among PLH experiencing homelessness/unstable housing who accessed care through (1) an incentivized, drop-in program (POP-UP) or (2) traditional primary care. We investigated 5 program features: single provider vs team of providers; visit incentives (0, 10, and 20); location (current site vs current + additional site); drop-in vs scheduled visits; in-person only vs optional telehealth visits; and navigator assistance. We estimated relative preferences using mixed-effects logistic regression and conducted latent class analysis to evaluate preference heterogeneity. Results: We enrolled 115 PLH experiencing homelessness/unstable housing, 40% of whom lived outdoors. The strongest preferences were for the same provider (β = 0.94, 95% CI: 0.48 to 1.41), visit incentives (β = 0.56 per 5; 95% CI: 0.47 to 0.66), and drop-in visits (β = 0.47, 95% CI: 0.12 to 0.82). Telehealth was not preferred. Latent class analysis revealed 2 distinct groups: 78 (68%) preferred a flexible care model, whereas 37 (32%) preferred a single provider. Conclusions: We identified heterogeneous care preferences among PLH experiencing homelessness/unstable housing during the COVID-19 pandemic, with two-thirds preferring greater flexibility and one-third preferring provider continuity. Telehealth was not preferred, even with navigator facilitation. Including patient choice in service delivery design can improve care engagement, particularly for marginalized populations, and is an essential tool for ending the HIV epidemic.